2017
DOI: 10.3892/mmr.2017.7799
|View full text |Cite
|
Sign up to set email alerts
|

Apurinic/apyrimidinic endonuclease 1 (APE1) contributes to resveratrol-induced neuroprotection against oxygen-glucose deprivation and re-oxygenation injury in HT22 cells: Involvement in reducing oxidative DNA damage

Abstract: Resveratrol, a naturally occurring polyphenolic compound, exhibits a neuroprotective role in models of central nervous system diseases, including cerebral ischemia/reperfusion injury. Apurinic/apyrimidinic endonuclease 1 (APE1) is a multifunctional enzyme that contributes to base excision repair of oxidative DNA damage and redox activation of transcription factors, associated with neuronal survival against hypoxic‑ischemic injury. It was hypothesized that resveratrol protects HT22 cells against oxygen‑glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
1
3
0
1
Order By: Relevance
“…Leak et al have also revealed that the upregulation of APE1, either endogenously or through transgene overexpression, reduces oxidative DNA damage and protects neurons against acute ischemic damage ( Leak et al, 2015 ). Consistent with prior studies, Jia et al have found that RES obviously elevated the activity and level of APE1 ( Jia et al, 2017 ). On the other hand, previous research has shown that strand breaks of apurinic/apyrimidinic sites are considered a marker of oxidative DNA damage, and 8-OHdG is also the specific product of DNA oxidative damage ( Chen et al, 1997 ; Lan et al, 2003 ).…”
Section: Molecular Mechanisms Of Res On Cvdsupporting
confidence: 88%
See 1 more Smart Citation
“…Leak et al have also revealed that the upregulation of APE1, either endogenously or through transgene overexpression, reduces oxidative DNA damage and protects neurons against acute ischemic damage ( Leak et al, 2015 ). Consistent with prior studies, Jia et al have found that RES obviously elevated the activity and level of APE1 ( Jia et al, 2017 ). On the other hand, previous research has shown that strand breaks of apurinic/apyrimidinic sites are considered a marker of oxidative DNA damage, and 8-OHdG is also the specific product of DNA oxidative damage ( Chen et al, 1997 ; Lan et al, 2003 ).…”
Section: Molecular Mechanisms Of Res On Cvdsupporting
confidence: 88%
“…In addition, the knockdown of APE1 blocked the neuroprotective and antioxidant effects of RES. The above results further showed that RES exerted a neuroprotective role in ischemic stroke, which was related to the APE1-induced oxidative DNA damage reduction and antioxidant defense system enhancement ( Jia et al, 2017 ) ( Figure 3 ).…”
Section: Molecular Mechanisms Of Res On Cvdmentioning
confidence: 64%
“…In addition, the overexpression of APE1 induced by an APE-mimicking peptide or adenovirus-mediated APE1 following reperfusion increased dNA repair, attenuated apoptosis and reduced the infarct volume (20,21). It has also been demonstrated that APE1 is an attractive target for neuroprotection and is involved in neuroprotection against cerebral I/R injury (22,23). Stetler et al (23) revealed that APE1 was required for pituitary adenylate cyclase-activating polypeptide (PAcAP)-induced neuroprotection against global cerebral ischemia.…”
Section: Curcumin Exerts Protective Effects Against Hypoxia-reoxygenamentioning
confidence: 99%
“…Both the endonuclease and transcription factor binding activities of APE1/Ref-1 result in increased resilience of cells to proapoptotic stimuli (reviewed in [11]). Resveratrol (RESV), a naturally occurring polyphenolic compound found in red wine and grapes, reportedly affects the redox activity of APE1/Ref-1 [12][13][14][15]. RESV was shown to inhibit the redox and endonuclease activities of APE1/Ref-1 in in vitro assays.…”
Section: Introductionmentioning
confidence: 99%